2020
DOI: 10.1136/gutjnl-2020-322179
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on UK endoscopic activity and cancer detection: a National Endoscopy Database Analysis

Abstract: ObjectiveThe COVID-19 pandemic has had a major global impact on endoscopic services. This reduced capacity, along with public reluctance to undergo endoscopy during the pandemic, might result in excess mortality from delayed cancer diagnosis. Using the UK’s National Endoscopy Database (NED), we performed the first national analysis of the impact of the pandemic on endoscopy services and endoscopic cancer diagnosis.DesignWe developed a NED COVID-19 module incorporating procedure-level data on all endoscopic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

32
300
5
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(343 citation statements)
references
References 17 publications
32
300
5
6
Order By: Relevance
“…The COVID-19 pandemic has had an extraordinary impact on the delivery of GI endoscopy, with an initial reduction to 12% of prepandemic levels in the UK. 1 In the deceleration and early recovery phases (up to end July 2020), this had risen to 42% of repandemic levels. 2 Recovery has been influenced by multiple factors including availability of staff, restrictions caused by longer room cleansing, physical distancing and the use of personal protective equipment (PPE) slowing lists.…”
Section: In More Detailmentioning
confidence: 99%
“…The COVID-19 pandemic has had an extraordinary impact on the delivery of GI endoscopy, with an initial reduction to 12% of prepandemic levels in the UK. 1 In the deceleration and early recovery phases (up to end July 2020), this had risen to 42% of repandemic levels. 2 Recovery has been influenced by multiple factors including availability of staff, restrictions caused by longer room cleansing, physical distancing and the use of personal protective equipment (PPE) slowing lists.…”
Section: In More Detailmentioning
confidence: 99%
“…The results of a recently published UK endoscopy database analysis have revealed that endoscopic activity reduced to 12% of pre-COVID levels, and at its low point, activity was only 5%. 3 The weekly number of cancers detected decreased by 58% and the proportion of missing cancers ranged from 19% (pancreatobiliary) to 72% (colorectal) according to the database analysis. 3 A multicentre survey in Italy conducted at the peak of the pandemic also revealed that majority of the units (60.5%) which had normal endoscopic activities reduced by 75-99%.…”
mentioning
confidence: 91%
“…3 The weekly number of cancers detected decreased by 58% and the proportion of missing cancers ranged from 19% (pancreatobiliary) to 72% (colorectal) according to the database analysis. 3 A multicentre survey in Italy conducted at the peak of the pandemic also revealed that majority of the units (60.5%) which had normal endoscopic activities reduced by 75-99%. 4 The results of web-based survey of gastroenterologists across North America also suggest that at the time of response (April 2020), most centres (46/71, 65%) were operating at ≤ 10% of their normal endoscopy volume.…”
mentioning
confidence: 91%
“…During the first wave, endoscopy activity has been limited to mostly emergency procedures. A recent study from the UK National Endoscopy Database, which is populated by automated real-time capture of endoscopy reports and contains over 2.5 million endoscopy records, revealed that the first weeks of the UK lockdown saw a reduction in endoscopy activity to 5 % of normal, with activity only recovering to 20 % of pre-COVID-19 levels in the subsequent weeks 1 . After the lockdown, endoscopy services face two immense challenges: 1) the adaptation of endoscopy units and workflows to COVID-19 prevention measures, which include social distancing, enforced downtime, and additional cleaning between procedures, all of which reduce patient throughput; and, simultaneously, 2) the absorption of all postponed procedures into the already overloaded endoscopy agenda.…”
mentioning
confidence: 99%
“…Indeed, a recent modeling study indicated that even modest delays in cancer surgery of 3 to 6 months might significantly impact survival, particularly for stage 2 or 3 cancers 3 . As a matter of fact, the recent article from the UK National Endoscopy Database revealed a dramatic and worrying effect of the fall in endoscopy activity on cancer diagnosis, with up to 72 % of expected CRCs not being detected 1 . Accordingly, major concern has arisen regarding the appropriateness of interruptions to such valuable programs.…”
mentioning
confidence: 99%